School screening programme in Mysore city - Shailaja Nikam (Journal of All India Institute of Speech and Hearing, 1970)
This is an interim report on the screening tests done for hearing loss  in the school children of Mysore city.   In a parallel study which is a collaborative project with the Junior Jaycees of Mysore, school going children in the rural areas are tested.   The results of the rural screening programme will be reported separately.